The Impact of Digital Transformation on Manufacturing Enterprises Innovation - Chen, Xiulian (Pacific International Journal, 2024)
With the rapid development of big data, artificial intelligence and other information technologies, the world economy is entering a new economic era driven by digital technology. Under the background of China Manufacturing 2025, the new generation of digital technology has had a fundamental impact on the reform of China’s manufacturing productivity. It also provides a strong driving force for China’s manufacturing industry to achieve high-quality development. At present, how to give full play to the driving role of digital innovation elements and achieve performance improvement has become a key concern of the country and enterprises. Based on the data of A-share listed manufacturing enterprises from 2007 to 2021, this paper uses multiple perspectives to measure the digital transformation of enterprises, uses the fixed effect model to verify the promotion effect of digital transformation on innovation, and further uses the multi-period DID model to verify the impact of digital transformation on the innovation performance of manufacturing enterprises through the parallel trend test. Through the empirical test, it is found that digital transformation can significantly promote the improvement of enterprise innovation performance. The research conclusions not only further enrich the relevant research on enterprise innovation under the background of digital transformation, but also provide a theoretical basis for the formulation and implementation of enterprise digital transformation strategy, have certain policy implications, and have certain reference value for manufacturing enterprises to better carry out digital transformation practice.